Search for s-channel single-top-quark production in events with missing energy plus jets in pp collisions at sqrt[s] = 1.96 TeV. - Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; Ashmanskas, W; et al. (2014)
The first search for single-top-quark production from the exchange of an s-channel virtual W boson using events with an imbalance in the total transverse energy, b-tagged jets, and no identified leptons is presented. Assuming the electroweak production of top quarks of mass 172.5 GeV/c(2) in the s channel, a cross section of 1.12(-0.57)(+0.61) (stat+syst) pb with a significance of 1.9 standard deviations is measured. This measurement is combined with the result obtained from events with an imbalance in total transverse momentum, b-tagged jets, and exactly one identified lepton, yielding a cross section of 1.36(-0.32)(+0.37) (stat+syst) pb, with a significance of 4.2 standard deviations.